Case Report: Takotsubo Cardiomyopathy in Bickerstaff Brainstem Encephalitis Triggered by COVID-19 - Kimura, Mizuki; Hashiguchi, Shunta; Tanaka, Kenichi; Hagiwara, Manato; Takahashi, Keita; Miyaji, Yosuke; Joki, Hideto; Doi, Hiroshi; Koga, Michiaki; Takeuchi, Hideyuki; Tanaka, Fumiaki (Frontiers in Neurology, 2021)
Takotsubo cardiomyopathy (TCM) is a stress-induced cardiomyopathy triggered by critical illness including severe neurological disorders. However, an association between TCM and Bickerstaff brainstem encephalitis (BBE) has rarely been described. During the current coronavirus disease 2019 (COVID-19) pandemic, growing evidence indicates that COVID-19 often leads to various neurological disorders, but there are few reports of an association between COVID-19 and BBE. Here we report a case of TCM associated with BBE triggered by COVID-19, which subsided with immunotherapy for BBE. Both transthoracic echocardiography and electrocardiography led to early and accurate diagnosis of TCM. Sustained hemodynamic instability due to TCM was immediately lessened with immunotherapy whereas additional plasmapheresis and immunotherapy were required to treat BBE. This case indicates that BBE might follow COVID-19 and TCM should be considered when hemodynamic status remains unstable in a patient with BBE.